Health Status Comparison of Blood Cockle (Tegillarca granosa) between Low and High Yield Farms in Selangor and Johor. Issue 1 (November 2021) - Yusuff, F M; Shari, M A M; Joni, A A M; Kusin, F M; Mohamed, K N; Zulkeflee, Z; Asha'ari, Z H; Zulkifli, S Z; Ismail, A; Arshad, A
Abstract: This study aims to provide insight knowledge on the potential reason for low blood cockles ( Tegillarca granosa ) production in Sungai Buloh Selangor by comparing the condition indices and histology of the gills and gonad with samples from a high yield farm at Sungai Ayam, Johor. Samples were collected in September 2020 and grouped for histological analysis and for condition indices. About 60% individuals from Sungai Buloh and 20% of samples from Sungai Ayam found with degenerated gill filaments. The sex ratio were found identical (50%:50% male to a female) in samples from Sungai Ayam, while 40%: 60% of male to female from Sungai Buloh. The gonad of males found at Stage 2 (developing) and Stage 3 (developed or ripe) and the ovaries at Stage 3 and Stage 4 (spawning) for Sungai Buloh, and between Stage 2 to Stage 4 from Sungai Ayam. The total condition index (CI Tot) was significantly differences between farms. Findings indicate sample from Sungai Buloh has low health status due to poor gill's filaments condition, and ripe ovaries found in lightweight (2 g) T. granosa . Hence being the potential reason for low survival rate in the Sungai Buloh.